Faktor Risiko Kejadi TB Paru - Hara, Maria Kareri (Poltekkes Kemenkes Kupang, 2021)
Background: Pulmonary Tuberculosis (TB) remains a major public health issue worldwide, including in Indonesia, with a continuously increasing incidence rate. Objective: This study aims to analyze the risk factors influencing the occurrence of pulmonary TB through a literature review approach. Method: The research accessed two databases, Google Scholar and PubMed. The search results yielded 8,350 articles from Google Scholar and 6,390 articles from PubMed. After screening and selection, 6 relevant journals from Google Scholar and 1 journal from PubMed were included for analysis. Results: The results indicate that the most significant risk factors for the occurrence of pulmonary TB are: 1) overcrowding, 2) low levels of education and knowledge, 3) inadequate lighting, and 4) poor nutritional status. These findings underscore the importance of prevention efforts involving both government and community participation, especially in addressing the risk factors that exacerbate the spread of TB in Indonesia.